Molecular Mechanisms of GPCR Signaling: A Structural Perspective - Gurevich, Vsevolod V. (Int J Mol Sci, 2017)
G protein-coupled receptors (GPCRs) are cell surface receptors that respond to a wide variety of stimuli, from light, odorants, hormones, and neurotransmitters to proteins and extracellular calcium. GPCRs represent the largest family of signaling proteins targeted by many clinically used drugs. Recent studies shed light on the conformational changes that accompany GPCR activation and the structural state of the receptor necessary for the interactions with the three classes of proteins that preferentially bind active GPCRs, G proteins, G protein-coupled receptor kinases (GRKs), and arrestins. Importantly, structural and biophysical studies also revealed activation-related conformational changes in these three types of signal transducers. Here, we summarize what is already known and point out questions that still need to be answered. Clear understanding of the structural basis of signaling by GPCRs and their interaction partners would pave the way to designing signaling-biased proteins with scientific and therapeutic potential.